Autistic and neurotypical variance in the appraisal of emotional and interoceptive words - von Hausen, Felipe; Larraín-Valenzuela, María Josefina; Carcamo, Benjamin; Salgado-Obregon, Natalia (Frontiers in Communication, 2025)
IntroductionThis study investigates how neurotype influences the emotional appraisal of words.MethodsA total of 131 Spanish-speaking adults in Chile (63 autistic and 68 neurotypical) rated on a 7-point Likert scale 238 Spanish nouns across six affective dimensions: (a) valence, (b) arousal, (c) subjective frequency, (d) association with depression, (e) association with anxiety, and (f) association with anger. Descriptive statistics and Principal Component Analysis were used to identify differences in lexical-affective ratings.ResultsThe results revealed consistent group differences in the emotional interpretation of words. Autistic participants tended to assign higher ratings to emotionally intense, concrete, and interoceptively salient terms, particularly those linked to bodily sensations, anxiety, or arousal. Words such as inquietud (uneasiness), ducha (shower), and ansia (craving) were rated as systematically more emotionally charged by autistic participants. In contrast, neurotypical participants favored abstract, socially embedded terms like admiración (admiration), soledad (loneliness), and decepción (disappointment), which rely more heavily on symbolic inference and social scripts. These differences were especially marked in the anxiety and arousal dimensions. Modeling results further confirmed that neurotype predicted systematic variation in ratings across all dimensions, suggesting distinct cognitive-emotional frameworks.DiscussionThe findings support the hypothesis that autistic and neurotypical individuals construct emotional meaning through different experiential systems: one grounded in interoception and perceptual salience, and the other guided by social abstraction. These insights offer implications for inclusive pedagogy, clinical communication, and the design of affective tools in education and therapy. Recognizing neurotype-specific emotional semantics may help reduce miscommunication and foster more adaptive and respectful forms of interaction across neurodivergent and neurotypical populations.